2014
DOI: 10.1007/s00216-014-7944-z
|View full text |Cite
|
Sign up to set email alerts
|

A new ELISA for the quantification of equine procalcitonin in plasma as potential inflammation biomarker in horses

Abstract: In human medicine, procalcitonin (PCT) is a very common and well-established biomarker for sepsis. Even though sepsis is also a leading cause of death in foals and adult horses, up to now, no data about the role of equine PCT in septic horses has been available. Based on monoclonal antibodies targeted against human PCT, we report here the development of a sandwich ELISA for the quantification of equine PCT in equine plasma samples. The ELISA was characterized for intra- and interassay variance and a working ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 16 publications
6
38
1
2
Order By: Relevance
“…High disease prevalence and economic impact have been described for equine chronic respiratory disease, therefore new biomarkers may help to differentiate these pneumopathies and to identify cases of subclinical disease. A species specific ELISA for equine PCT (ePCT) was established [20], which allows quantitative measurements instead of gene expression with a high specificity and sensitivity. High ePCT concentrations were found in plasma of endotoxemic horses suffering from colic [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…High disease prevalence and economic impact have been described for equine chronic respiratory disease, therefore new biomarkers may help to differentiate these pneumopathies and to identify cases of subclinical disease. A species specific ELISA for equine PCT (ePCT) was established [20], which allows quantitative measurements instead of gene expression with a high specificity and sensitivity. High ePCT concentrations were found in plasma of endotoxemic horses suffering from colic [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Auch bei Hamstern, Schweinen, Ratten und Affen wurde ein PCT-Anstieg nach experimentell induzierter Endotoxämie beobachtet, was PCT zu einem möglichen Biomarker für bakterielle Entzündungen in der Veterinärmedizin macht (Zannoni et al 2012, Redl et al 2001, Wagner et al 2002. Beim Pferd konnten in Untersuchungen bei septischen (Rieger et al 2014) …”
Section: Introductionunclassified
“…The authors argued that PCT is not expressed by leucocytes to a high degree, while Toribio [23] described the very complex composition of the CALC-I-gene and questioned the primer sequences in the PCR used. The species specific ELISA used in our study however has been found to have a high sensitivity even in horses, in which sepsis was questionable [17]. In a study on colic patients high concentrations were found using this ELISA as well [27].…”
Section: Discussionmentioning
confidence: 53%
“…Rieger et al established a new species specific ELISA for equine PCT, which allows evaluating the actual PCT concentration and not only its gene expression with a high specifity and sensitivity [17]. We figured that this biomarker might allow reducing antibiotic treatment in the long term and shorten the duration of therapy in affected foals.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation